Entrepreneurship education and entrepreneurial competencies among university students / Nurul Nadia Nazari and Shamsul Huda Abd Rani - Nazari, Nurul Nadia; Abd Rani, Shamsul Huda (UiTM Cawangan Kedah, 2022)
This paper highlights the relationship between entrepreneurship education and entrepreneurial competencies among students. It has been known that entrepreneurial competencies among graduates are still questionable and still largely unexplained. Entrepreneurship competencies may help the graduates to reduce the unemployment rate. Entrepreneurship education was represented by teaching method and infrastructure facilities and resources. A number of 108 students of Bachelor of Entrepreneurship (Hons.), Universiti Utara Malaysia (UUM) Sintok were identified as the sample of the study. Data has been analysed using Pearson Correlation and multiple regression analysis under Statistical Package of Social Science (SPSS). The results have shown entrepreneurship education dimension that consists of teaching methods and infrastructure facilities have positive relationship with entrepreneurial competencies among students.